1984
DOI: 10.1152/jn.1984.51.1.164
|View full text |Cite
|
Sign up to set email alerts
|

Model of electroretinogram b-wave generation: a test of the K+ hypothesis

Abstract: Generation of the electroretinogram b-wave is simulated with a computer model representing a dark-adapted amphibian retina. The simulation tests the K+ hypothesis of b-wave generation, which holds that b-wave currents arise from localized Müller cell depolarizations generated by light-evoked increases in extracellular K+ concentration, [K+]o. The model incorporates the following components and processes quantitatively: 1) two time-dependent K+ sources representing the light-evoked [K+]o increases in the inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
4

Year Published

1984
1984
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(102 citation statements)
references
References 34 publications
4
94
0
4
Order By: Relevance
“…Latent b-wave responses mark the initial events in retinal dysfunction and have been shown to occur in the early stages of degenerative retinal syndromes including diabetic retinopathy (7,40), retinitis pigmentosa (19), and retinal ischemia (6). b-wave function results from the flow of current from the photoreceptor cell layers of the retina into the vitreous via the Müller cell in response to a visual stimulus (33). The Müller cell, which spans the length of the retina, provides architectural support and regulates neurotransmitter levels in the retina by degrading or removing these substances during neuronal activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Latent b-wave responses mark the initial events in retinal dysfunction and have been shown to occur in the early stages of degenerative retinal syndromes including diabetic retinopathy (7,40), retinitis pigmentosa (19), and retinal ischemia (6). b-wave function results from the flow of current from the photoreceptor cell layers of the retina into the vitreous via the Müller cell in response to a visual stimulus (33). The Müller cell, which spans the length of the retina, provides architectural support and regulates neurotransmitter levels in the retina by degrading or removing these substances during neuronal activity (36).…”
Section: Discussionmentioning
confidence: 99%
“…Within the central nervous system (CNS) Kir4.1 is expressed in glia, including the principal glial cell type in the retina, the M€ uller cell (Kofuji et al, 2000). Kir4.1 is implicated in the process of ''potassium siphoning'' (Newman and Odette, 1984), a mechanism of potassium buffering that helps stabilize the extracellular potassium concentration ([K 1 ] o ) in the face of neuronallyderived ion fluxes (Amedee et al, 1997;Kofuji et al, 2000;Kofuji and Connors, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We have suggested that the retinal Müller cell, a specialized astrocyte that spans nearly the entire width of the retina, buffers changes in retinal [K + ] o (4,5). We have shown that amphibian Müller cells are almost exclusively permeable to K + (6) and that 94 percent of the total K + conductance in these cells occurs in the Müller cell endfoot, a process lying adjacent to the vitreous humor (4).…”
mentioning
confidence: 99%